(untitled) (Revista de Ciências Agroveterinárias, 2008)
With the fast increase in plant population, there is a need to enhance current rice productivity levels to feed the 8.9 billion people estimated to live on earth by 2010. During the last 30 years, the population of Asian countries that grow and consume more than 90% of rice world production increased nearly 30%. Fortunately, rice production on these countries doubled in the same period due to the use of modern cultivars and hybrids with high grain yield potential. This review aimed to discuss important issues to the future of breeding programs and the development of rice hybrids. It discusses subjects such as breeding for the three lines and two-line systems, genetic citoplasmatic male sterility, male sterility caused by the environment, restoring genes and the advantages and disadvantages inerent to each method.